2023
DOI: 10.3389/fendo.2023.1143736
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Better late than never, but sooner is better: switch from CSII to sulfonylureas in two patients with neonatal diabetes due to KCNJ11 variants

Abstract: Neonatal diabetes mellitus (NDM) is a rare genetic disease characterized by severe hyperglycemia requiring insulin therapy with onset mostly within the first 6 months and rarely between 6-12 months of age. The disease can be classified into transient (TNDM) or permanent neonatal diabetes mellitus (PNDM), or it can be a component of a syndrome. The most frequent genetic causes are abnormalities of the 6q24 chromosomal region and mutations of the ABCC8 or KCNJ11 genes coding for the pancreatic beta cell’s potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Following international guidelines, the administration of oral sulfonylurea medications is the recommended therapy in recognized NDM, particularly in cases caused by channelopathies. The use of oral SU remains a highly effective treatment in 90% of NDM cases; among them, glibenclamide has the most promising research [22]. The facts are clear-cut: prompt treatment of NDM benefits child growth and weight gain, and it is crucial for the long-term development of a child.…”
Section: Discussionmentioning
confidence: 99%
“…Following international guidelines, the administration of oral sulfonylurea medications is the recommended therapy in recognized NDM, particularly in cases caused by channelopathies. The use of oral SU remains a highly effective treatment in 90% of NDM cases; among them, glibenclamide has the most promising research [22]. The facts are clear-cut: prompt treatment of NDM benefits child growth and weight gain, and it is crucial for the long-term development of a child.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the benefits of CSII and CGM in patients with NDM ( 10 , 15 , 17 , 19 , 35 ). Three previous studies have shown that CGM is useful not only for insulin therapy, but also for switching to oral SU in patients with NDM with the KCNJ11 variant ( 19 , 35 , 36 ). Li et al reported the feasibility of switching to oral SU therapy before genetic testing ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary and maintenance doses of SU differ individually, depending mainly on the genetic variant ( 22 , 24 , 26 , 29 ). Some clinical reports have indicated differences in the frequency (2–6 times a day) and dose (0.18–3.0 mg/kg/d at response dose) of glibenclamide ( 19 , 26 , 35 , 36 ). These studies used CGM to adjust the dose and frequency of glibenclamide ( 19 , 35 , 36 ) but did not apply long-term CGM monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation